Weichselian and Holocene palaeoenvironmental history of the Bol'shoy Lyakhovsky Island, New Siberian Archipelago, Arctic Siberia. - Andreev, Andrei A; Grosse, Guido; Schirrmeister, Lutz; Kuznetsova, Tatyana V; Kuzmina, Svetlana A; Bobrov, Anatoly A; Tarasov, Pavel E; Novenko, Elena Y; Meyer, Hanno; Derevyagin, Aleksandr Yu; Kienast, Frank; Bryantseva, Anna; et al. (PANGAEA, 2010)
Cryolithological, ground ice and fossil bioindicator (pollen, diatoms, plant macrofossils, rhizopods, insects, mammal bones) records from Bol'shoy Lyakhovsky Island permafrost sequences (73°20'N, 141°30'E) document the environmental history in the region for the past c. 115 kyr. Vegetation similar to modern subarctic tundra communities prevailed during the Eemian/Early Weichselian transition with a climate warmer than the present. Sparse tundra-like vegetation and harsher climate conditions were predominant during the Early Weichselian. The Middle Weichselian deposits contain peat and peaty soil horizons with bioindicators documenting climate amelioration. Although dwarf willows grew in more protected places, tundra and steppe vegetation prevailed. Climate conditions became colder and drier c. 30 kyr BP. No sediments dated between c. 28.5 and 12.05 14C kyr BP were found, which may reflect active erosion during that time. Herb and shrubby vegetation were predominant 11.6-11.3 14C kyr BP. Summer temperatures were c. 4 °C higher than today. Typical arctic environments prevailed around 10.5 14C kyr BP. Shrub alder and dwarf birch tundra were predominant between c. 9 and 7.6 kyr BP. Reconstructed summer temperatures were at least 4 °C higher than present. However, insect remains reflect that steppe-like habitats existed until c. 8 kyr BP. After 7.6 kyr BP, shrubs gradually disappeared and the vegetation cover became similar to that of modern tundra. Pollen and beetles indicate a severe arctic environment c. 3.7 kyr BP. However, Betula nana, absent on the island today, was still present. Together with our previous study on Bol'shoy Lyakhovsky Island covering the period between about 200 and 115 kyr, a comprehensive terrestrial palaeoenvironmental data set from this area in western Beringia is now available for the past two glacial-interglacial cycles.
Pollen records from Bol'shoy Lyakhovsky Island, Siberia
Keywords: 1TZ1; 2TZ2; 3TZ; 3TZ1; 3TZ2; 3TZ5; AWI_PerDyn; Bolshoy Lyakhovsky Island, East Siberia, Russia; Geological profile sampling; GEOPRO; L11; Permafrost Research (Periglacial Dynamics) @ AWI